Kajian Ilmu Falak dan Astronomi Dalam Sudut Pandang Filsafat Ilmu - Lauhatun Nashiha; Mahsun Mahsun (Islamic Astronomy Department, Sharia and Law Faculty, 2024)
At first Ilmu Falak was no different from Astronomy. The study of astronomy is as broad as astronomy. However, over time there has been a narrowing of studies in Ilmu Falak. Why is that? Does that make it different from astronomy? This paper will discuss this using a philosophical approach. Data were obtained from various literatures which were then analyzed. This research attempts to study astronomy from a philosophical point of view